The Patient Lived-Experience of Ventral Capsulotomy for Obsessive-Compulsive Disorder: An Interpretive Phenomenological Analysis of Neuroablative Psychiatric Neurosurgery - Barrios-Anderson, Adriel; McLaughlin, Nicole C. R.; Patrick, Morgan T.; Marsland, Richard; Noren, Georg; Asaad, Wael F.; Greenberg, Benjamin D.; Rasmussen, Steven (Frontiers in Integrative Neuroscience, 2022)
Ventral Capsulotomy (VC) is a surgical intervention for treatment-resistant Obsessive-Compulsive Disorder (OCD). Despite clinical studies, little is known about patient perception and lived experience after neurosurgery for severe OCD. To examine the lived experiences of patients who have undergone VC for severe, treatment-resistant OCD through qualitative analysis. We conducted semi-structured interviews with six participants treated with VC for OCD. Interviews were analyzed using Interpretive Phenomenological Analysis. The following themes emerged: (1) After years of conventional treatments, patients felt neurosurgery was their “last hope” and described themselves as “desperate,” (2) While some described the surgery as a “supernatural experience,” patients also demonstrated understanding of the scientific procedure, its risks and potential benefits, (3) The surgical experience itself was positive or neutral, which was linked to trust in the clinical team, (4) Post-surgery, participants described months of heightened fear as they awaited lesion formation and functional improvement. (5) Patients consistently contextualized outcome in the context of their own life goals. Patients undergoing VC have positive views of this neurosurgical intervention, but psychiatric neurosurgical teams should anticipate patient discomfort with the time needed to achieve behavioral improvement following surgery and emphasize the importance of post-operative psychiatric care.